Gas adsorption, thermal and structural properties of sinters made of fine silver powder for ultra-low-temperature heat exchangers. (September 2019) - Nakagawa, Hisashi; Miseki, Yugo; Akoshima, Megumi
Highlights: Pure fine silver powder sinter heat exchanger materials were studied. Bond strength between particles in a sinter was assessed using thermal diffusivity. A 0.13 μm sinter had surface area 1.4 m 2 /g and pore volume 5.99 × 10 −3  cm 3 /g. A 0.13 μm sinter showed bond strength equal to that of a common 0.07 μm material. The 0.13 μm sinter is suitable for use in ultra-low-temperature cooling. Abstract: This work investigated sinters made of pure fine silver powders having nominal particle sizes of 0.07, 0.13 and 10.6 μm, using nitrogen gas adsorption, laser flash analysis and field emission-scanning electron microscopy. The goal was to improve the efficiency of heat exchangers used in ultra-low-temperature cooling. This study also examined the bond strength between particles in the sinters, which is associated with the thermal conductivity of the materials, based on thermal diffusivity data. The 0.13 μm sinter had a specific surface area greater than 1.4 m 2 /g, while the 0.07 μm material, which is most widely used for ultra-low-temperature cooling, had a value of approximately 0.4 m 2 /g. The latter surface area was less than 25% of previously reported values. The 0.13 μm sinter with a 55% packing fraction exhibited a large total pore volume of 5.99 × 10 −3  cm 3 /g, a high specific surface area of 1.6 m 2 /g, and the largest room temperature intrinsic thermal diffusivity of 9.12 × 10 −5  m 2 /s in air. Therefore, the 0.13 μm material represents the optimal heat exchange sinter for ultra-low-temperature applications.